Colonial Historiography of Malabar: Towards an Alternative to History - Abraham, Renu Elizabeth (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
This article aims to assess the impact of colonial historiography on precolonial modes of knowledge from Malabar. It examines the colonial writing of the early history of Malabar based on a local tradition centered on Cēramān Perumāḷ in manuals and gazetteers produced in British Malabar and the Indian princely states of Cochin and Travancore in the late nineteenth and early twentieth centuries. The colonial-era historians interpreted the contradictions contained in the Perumāḷ tradition as signs of an ahistorical society. This study offers a critique of the conception of ahistoricity and argues that the colonial attempt to historicize the Perumāḷ tradition reveals a gap between Western positivist history and local mythmaking. It reads the contradictions as integral to the tradition and finds that they offer a window into the heterogeneous contexts in which the Perumāḷ served as a founder-hero for rival political, economic, and religious stakeholders in Indian Ocean trade since the twelfth century.